ANALYSIS OF THE EFFECT OF COMPANY SIZE, COMPANY AGE AND AUDIT OPINION ON THE TIMELINESS OF FINANCIAL REPORT - Satiman, Satiman; Ramdani, Edon; Suparmin, Suparmin (Universitas Putera Batam, 2025)
This study aims to determine the effect of Company Size, Company Age and Audit Opinion on the Timeliness of Financial Reporting in transportation and logistics sector companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. The type of research used is quantitative (secondary) research that is causal comparative. In this study, the number of samples was 11 companies obtained by purposive sampling method. Data samples were obtained from 55 data for 5 years. The data analysis technique used is descriptive statistics and panel data regression analysis. This research was processed using Eviews-12 software. The results of this study are based on a partial test with the T test and show that (1) Company size has no significant effect on the timeliness of financial reporting, (2) Company Age has a significant effect on the timeliness of financial reporting, (3) Audit Opinion has no significant effect on accuracy Time of Financial Reporting, Based on the simultaneous test with Test F states that Company Size, Company Age and Audit Opinion simultaneously affect the Timeliness of Financial Reporting.